Protective effect of total and supplemental vitamin C intake on the risk of hip fracture—a 17-year follow-up from the Framingham Osteoporosis Study - Sahni, S; Hannan, M. T; Gagnon, D; Blumberg, J; Cupples, L. A; Kiel, D. P; Tucker, K. L (Osteoporosis international, 2009)
Summary Vitamin C may play a role in bone health. In the Framingham Study, subjects with higher total or supplemental vitamin C intake had fewer hip fractures and non-vertebral fractures as compared to subjects with lower intakes. Therefore, vitamin C may have a protective effect on bone health in older adults. Introduction Dietary antioxidants such as vitamin C may play a role in bone health. We evaluated associations of vitamin C intake (total, dietary, and supplemental) with incident hip fracture and non-vertebral osteoporotic fracture, over a 15- to 17-year follow-up, in the Framingham Osteoporosis Study. Methods Three hundred and sixty-six men and 592 women (mean age 75 ± 5 years) completed a food frequency questionnaire (FFQ) in 1988-1989 and were followed for non-vertebral fracture until 2003 and hip fracture until 2005. Tertiles of vitamin C intake were created from estimates obtained using the Willett FFQ, after adjusting for total energy (residual method). Hazard ratios were estimated using Cox-proportional hazards regression, adjusting for covariates. Results Over follow-up 100 hip fractures occurred. Subjects in the highest tertile of total vitamin C intake had significantly fewer hip fractures (P trend = 0.04) and non-vertebral fractures (P trend = 0.05) compared to subjects in the lowest tertile of intake. Subjects in the highest category of supplemental vitamin C intake had significantly fewer hip fractures (P trend = 0.02) and non-vertebral fractures (P trend = 0.07) compared to non-supplement users. Dietary vitamin C intake was not associated with fracture risk (all P > 0.22). Conclusion These results suggest a possible protective effect of vitamin C on bone health in older adults.